Ocular Gnathostomiasis in A Farmer From South Sulawesi, Indonesia: Poster Presentation - Case Report - Resident - Dian Trisnawaty M (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ocular Gnathostomiasis is a rare parasitic infection caused by the third-stage larvae of the spiruroid nematode. It is a food-borne zoonosis caused by the consumption of raw or undercooked freshwater species of fish, amphibians, reptiles, birds, and mammals. Case Illustration : A 37-year-old farmer complained of seeing moving objects in his left eye accompanied by blurred vision. The patient had a history of red left eye with increased intraocular pressure. The visual acuity of the left eye was 20/30. Slit lamp examination showed slight hyperemia of the conjunctiva and a live worm moving in the anterior chamber. The worm was immediately removed using corneal clear incision and sent for parasitological examination. By finding four rows of hooks on the head and fine spines covering the body, the worm was identified as a stage 3 larva of gnathostome sp. Discussion : Surgical removal of the larvae is considered the most effective treatment. In this case, the patient was then treated with Albendazole 400 mg daily for 21 days and Prednisolone 50 mg for 7 days with reduced doses of 10 mg weekly for three weeks Conclusion : Ocular Gnathostomiasis by third-stage larvae of spiruroid nematode was found at the eye of a man from Siwa, South Sulawesi. The intracameral worm was successfully extracted from the eye. Patients with complaints of recurrent redness of the eyes accompanied by increased intraocular pressure and a history of living in an area with a habit of eating raw freshwater fish should be considered the possibility of harboring helminth in the eye.